Relationship between the metabolic and lipid profile in follicular fluid of women undergoing in vitro fertilization. Issue 9 (3rd September 2020) - Luti, Simone; Fiaschi, Tania; Magherini, Francesca; Modesti, Pietro A.; Piomboni, Paola; Governini, Laura; Luddi, Alice; Amoresano, Angela; Illiano, Anna; Pinto, Gabriella; Modesti, Alessandra; Gamberi, Tania
Abstract: Among the follicular fluid (FF) components promoting the development of the oocyte are included glycoproteins, several fatty acids, and steroid hormones synthesized by the dominant follicle. For this, the analysis of the metabolites present in FF can determine the quality of the oocyte. FF composition is in part determined by local follicular metabolic processes and in part a plasma transudate. Since the causes of impaired fertility may be due to a metabolic imbalance, metabolomics is useful to identify low molecular weight metabolites. Oxidative stress is involved in human infertility and the use of metabolomics can be crucial to identify which other metabolites besides reactive oxygen species are involved in oxidative stress correlated to infertility. To obtain new information on the study of signaling molecules in FF, the knowledge of the lipid content will be important to improve information on the understanding of follicular development. The objective of this study is to identify (a) a metabolic profile and a lipid profile of FF in women undergoing in vitro fertilization and (b) to correlate the previous information obtained regarding adiponectin and oxidative stress with the metabolic and lipid profile obtained in the present study. As result, we found an increase in oxidative stress due to both an increase of androgens and an accumulation of lipids in the follicular environment and we suggest that this might be one of the causes of reduced fertility. Abstract : We identify a metabolic profile and a lipid profile of follicular fluid we correlate adiponectin and oxidative stress with the metabolic and lipid profile we found an increase in oxidative stress due to an increase of androgens and an accumulation of lipids we suggest that this might be one of the causes of reduced fertility.